Historically Informed Performing Bach: Analysing and Mapping the Debate on the Scoring of Bach's Cantatas - Snellings, Dirk 1959-2014; Van Looy, Bart; Vervliet, Stijn (Leuven Acco, 2012)
This artistic research project analyses the ongoing debate on the vocal and instrumental scoring of Bachs cantatas. It reveals both similarities and differences by means of a content analysis of written accounts and a hierarchical class analysis. Thus, it is shown that adherence to historical sources does not necessarily lead to univocal interpretation, even within a community of historically informed performers. Eventually, this research project reveals an analogy with processes of research and creation as documented in innovation studies.About the authors:Dirk Snellings holds a masters degree in Musicology. He is currently teaching Singing and History of Early Music at the Lemmensinstituut Leuven. Besides having a career as a soloist, he is the founder, artistic director and bass of the ensemble Capilla Flamenca. He is af liated researcher at the Faculty of Arts and Architecture of the KU Leuven.Bart Van Looy is professor in the eld of Innovation and Organization at the Department of Managerial Economics, Strategy and Innovation of the KU Leuven. He is co-promotor of ECOOM and af liated with the School of Management and Governance, University of Twente.Stijn Vervliet holds a masters degree in Music. He is currently working as researcher and research coordinator at the Lemmensinstituut Leuven. He is a PhD student and af liated researcher at the Faculty of Arts and Architecture of the KU Leuven.
Keywords: Bach, Johann Sebastian -- 1685-1750; 18th Century (1701-1800); Cantata; Historically informed performance; Instrumentation; Germany